Implication of Crystal Water Molecules in Inhibitor Binding at ALR2 Active Site - Hymavati (Hindawi Publishing Corporation, 2012)
Water molecules play a crucial role in mediating the interaction between a ligand and a macromolecule. The solvent environment around such biomolecule controls their structure and plays important role in protein-ligand interactions. An understanding of the nature and role of these water molecules in the active site of a protein could greatly increase the efficiency of rational drug design approaches. We have performed the comparative crystal structure analysis of aldose reductase to understand the role of crystal water in protein-ligand interaction. Molecular dynamics simulation has shown the versatile nature of water molecules in bridge H bonding during interaction. Occupancy and life time of water molecules depend on the type of cocrystallized ligand present in the structure. The information may be useful in rational approach to customize the ligand, and thereby longer occupancy and life time for bridge H-bonding.